A Bioactive Living Hydrogel: Photosynthetic Bacteria Mediated Hypoxia Elimination and Bacteria‐Killing to Promote Infected Wound Healing. Issue 1 (30th July 2020) - Li, Wanlin; Wang, Shoujie; Zhong, Danni; Du, Zhen; Zhou, Min
Abstract: Disruption and vasoconstriction of the blood vessels that results in tissue hypoxia can retard the wound healing process. Transcutaneous oxygen delivery for the hypoxic tissue has been shown to be an effective method for enhanced wound regeneration, for example, hyperbaric oxygen therapy and topical oxygen therapy. However, these techniques' clinical applications are limited by high cost and complicated protocols. To combat this, a bioactive living hydrogel based on photosynthetic microorganisms is designed for enhanced wound healing by production and local delivery of oxygen to alleviate acute and chronic tissue hypoxia. Spirulina platensis (SP), a type of photosynthetic bacteria is coated with the natural polymer carboxymethyl chitosan to obtain the SP gel, which keeps the oxygen generation capability of the SP while promoting its adhesion to the infected wound. Moreover, chlorophyll, a natural photosensitizer, is released from the SP irradiated with 650‐nm laser, and generates reactive oxygen species, thereby causing photodynamic destruction of bacteria in the infectious area. Cytotoxicity assays and in vivo toxicity assessment demonstrate the excellent biocompatibility of the gel. The SP gel is easy to obtain, cheap for mass production, and convenient for usage, which is promising for clinical application. Abstract : The living photosynthetic microorganisms Spirulina platensis (SP) are coated with the naturally occurring polymer carboxymethyl chitosan to obtain a biocompatible SP gel. The SP gel can generate oxygen for hypoxia elimination and reactive oxygen species for sterilization of the wound area under 650‐nm laser irradiation. The SP gel mediates both oxygen delivery and photodynamic antibacterial therapy, significantly enhancing wound regeneration.